Identification and Immunological Characterization of Somatic Proteins from Adults of Toxocara cati by Proteomics Technique - Nooshinmehr SOLEYMANI; Ruth Birner GRUNBERGER; khalil ABNOUS; Hassan BORJI; Faezeh VAHDATI (Iranian Journal of Parasitology, 2021)
Background: Toxocara cati is considered as one of the main etiological agents of toxocariasis with global and regional importance. As there is no information on proteomics of T. cati, herein, we reported the results obtained by proteomic analysis of somatic proteins extract, using a mass spectrometry (LC–MS/MS) approach.